In silico screening and molecular analyses identify apigenin from Scutellaria barbata as a potent AKT1 inhibitor in breast cancer - Md. Maruf Khan; Md. Arju Hossain; Fatematuz Zohora; Md. Sohel; Md. Faisal Amin; Fatematuz Zuhura Evamoni; M. Nazmul Hoque (PLoS ONE, 2026)
Breast cancer (BC) remains a leading cause of cancer-related mortality in women worldwide. Scutellaria barbata , a traditional Chinese medicinal herb, possesses recognized anticancer properties, but its mechanistic role in BC is not fully elucidated. This study employed an integrated in silico approach to identify the key flavonoids, targets, and pathways through which S. barbata exerts its anti-BC effects. A multi-step computational methodology incorporating network pharmacology, molecular docking, and dynamics simulations was utilized to profile bioactive compounds from S. barbata . From an initial set of 34 phytocompounds, three flavonoids namely apigenin, 4’-hydroxywogonin, and hispidulin demonstrated favorable drug-likeness, high bioavailability, and low predicted acute oral toxicity (LD₅₀ > 500 mg/kg) profiles. Network analysis identified AKT1, IL6 and TNF as central hub targets, significantly enriched in the PI3K-Akt, MAPK, and TNF signaling pathways. Molecular docking showed strong binding affinities (≤ –7.5 kcal/mol) between these flavonoids and the hub proteins, with hispidulin (–8.1 kcal/mol) and apigenin (–7.7 kcal/mol) exhibiting the highest affinity for AKT1 than other hub proteins. Molecular dynamics simulations over 100 ns further revealed that the apigenin-AKT1 complexes exhibited greater stability with lower RMSD fluctuations, reduced residue flexibility (RMSF), stable radius of gyration, and consistent SASA profiles, compared to other ligands and the control compound. Our computational prediction suggests that apigenin exhibits favorable multi-target interactions with BC-associated proteins. Thus, apigenin may represent a potential candidate for further investigation, particularly with respect to oncogenic signaling pathways involving key hub proteins. However, experimental validation through in vitro and in vivo studies is required to confirm these observations.